1995
DOI: 10.1177/1357633x9500100107
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study of the Physician Acceptance of Tele-Oncology

Abstract: During the winter of 1993, medical oncologists from an urban, university-based hospital provided oncology care to rural patients using interactive video clinics (tele-oncology). In order to assess physician satisfaction with this form of outreach, surveys were performed after the video encounters, as well as after a limited number of subsequent clinical encounters on site. Various aspects of satisfaction were evaluated. Although the sample was small (a total of 41 clinical encounters and 3 oncologists), the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 3 publications
0
24
0
1
Order By: Relevance
“…[1][2][3][4] The lack of influence of bandwidth on patient satisfaction suggests that the quality of transmission provided at 1 ⁄4 T1 bandwidth was sufficient for good physician and patient rapport. Age proved to be an independent predictor of patient acceptance; older patients were less inclined to embrace the new technology.…”
Section: Patient Provider and Nurse-escort Impressionsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] The lack of influence of bandwidth on patient satisfaction suggests that the quality of transmission provided at 1 ⁄4 T1 bandwidth was sufficient for good physician and patient rapport. Age proved to be an independent predictor of patient acceptance; older patients were less inclined to embrace the new technology.…”
Section: Patient Provider and Nurse-escort Impressionsmentioning
confidence: 99%
“…Seven patients refused to participate. The reasons given included a dislike of machines (4), lack of time (2), and frustration with the skin problem (1). No obvious common characteristic explained their lack of participation.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…Several programs were initiated and ultimately established by proactive physicians who were in part motivated by factors interestingly different from those common to most rural-based telemedicine programs in the United States [32]. Driven mostly by urgent patient care demands and the needs for improved utilization efficiency (particularly in highly specialized facilities of limited service capacity), existing telemedicine programs in Hong Kong are largely urban-based and have a prominent tertiary care focus.In their fairly comprehensive review of previous telemedicine research, Perednia and Allen [39] commented that, because of a predominant focus on technological developments and clinical applications, most prior research has offered limited discussion on important issues pertaining to organizational and managerial consideration (for example [3]). As the authors concluded, the ultimate success of telemedicine as a viable service collaboration and delivery alternative or as a routine means for physicians to manage patient care requires health-care organizations to address both technological and managerial challenges.…”
mentioning
confidence: 99%
“…In their fairly comprehensive review of previous telemedicine research, Perednia and Allen [39] commented that, because of a predominant focus on technological developments and clinical applications, most prior research has offered limited discussion on important issues pertaining to organizational and managerial consideration (for example [3]). As the authors concluded, the ultimate success of telemedicine as a viable service collaboration and delivery alternative or as a routine means for physicians to manage patient care requires health-care organizations to address both technological and managerial challenges.…”
mentioning
confidence: 99%
“…A handful of studies have investigated physician (user) technology acceptance issue, but most of them were limited in terms of medical specialty or sample size and were conducted in an ad hoc manner [16][17][18][19][20]. As summarized by Mitchell et al [17], these investigations typically had a small and restrictive sample size and tested hypotheses that were idiosyncratically formulated without theoretical foundation.…”
Section: Literature Review and Research Motivationmentioning
confidence: 98%